Efeito do período de polimento sobre a superfície de resinas compostas: análise da propriedade óptica. - Fontes, Amanda Maslem [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
OBJECTIVE: To evaluate the influence of the polishing period on the color before and after thermal aging in four composite resins. MATERIAL AND METHOD: 240 specimens were made using the composite resins Durafill VS, Vittra APS, Filtek Z 350 XT and Spectra Smart to obtain twelve experimental groups (n = 20), of which they were distributed in 3 subgroups, according to the periods polishing (immediate, 7 and 21 days). G I - G IV had the surfaces polished immediately after making the specimens with the sequence of SofLex Pop On discs in decreasing order of granulation; G V - G VIII and G IX - G XII were stored at 100% humidity in a humidifying chamber with a temperature of 37 ° C for a period of 7 and 21 days, respectively. After the referred period, the specimens' surfaces received the polishing protocol. Afterwards, the color analysis was measured in the Visible Ultraviolet Reflection spectrophotometer *. After the initial analysis, the same specimens received 10,000 thermal cycles performed in a thermal cycling machine, configured for bathing in water at temperatures of 5 ° and 55 ° C, with a residence time of 30 seconds. Subsequently, the aged specimens were subjected to the same analysis. Two factors ANOVA were applied to the data obtained for repeated measures and Tukey's post-test (p <0.05). RESULTS: Color change (ΔE) was observed in all tested resins, and the highest values of ΔE were recorded in Durafill VS and Vittra APS resins in the polishing period 21 days (G IX and G X); The composite resin Z 350 XT showed an increase in the value of ΔE in the period of immediate polishing (G III) with that of 21 (G XI) and 7 days (G VII); Spectra Smart resin showed a significant difference only in the 7 days late polishing. CONCLUSION: The color property was directly influenced by the polishing periods, with nanoparticulate composite resins being the most susceptible to color changes after thermal aging.

OBJETIVO: Avaliar a influência do período de polimento na cor antes e após o envelhecimento térmico em quatro resinas compostas. MATERIAL E MÉTODO: Foram confeccionados 240 espécimes utilizando as resinas compostas Durafill VS, Vittra APS, Filtek Z 350 XT e Spectra Smart para obtenção de doze grupos experimentais (n=20), dos quais foram distribuídos em 3 subgrupos, de acordo com os períodos de polimentos (imediato, 7 e 21 dias). G I – G IV tiveram as superfícies polidas imediatamente após a confecção dos espécimes com a sequência de discos SofLex Pop On em ordem decrescente de granulação; G V – G VIII e G IX – G XII foram armazenados 100% de umidade em câmara umidificadora com temperatura de 37°C durante um período de 7 e 21 dias, respectivamente. Após o período referido, as superfícies dos espécimes receberam o protocolo de polimento. Na sequência a análise da cor foi mensurada no espectrofotômetro de Reflexão Ultravioleta Visível*. Após a análise inicial, os mesmos espécimes receberam 10.000 ciclos térmicos realizados em máquina de ciclagem térmica, configurada para banhos em água em temperaturas de 5° e 55°C, com tempo de permanência de 30 segundos. Posteriormente, os espécimes envelhecidos foram submetidos à mesma análise. Nos dados obtidos foi aplicado ANOVA dois fatores para medidas repetidas e pós-teste de Tukey (p<0,05). RESULTADOS: Alteração de cor (ΔE) foi observada em todas resinas testadas, sendo que os maiores valores de ΔE foram registrados nas resinas Durafill VS e Vittra APS no período de polimento 21 dias (G IX e G X); A resina composta Z 350 XT evidenciou acréscimo no valor do ΔE no período de polimento imediato (G III) com o de 21 (G XI) e 7 dias (G VII); A resina Spectra Smart mostrou diferença significativa apenas no polimento tardio de 7 dias. CONCLUSÃO: A propriedade cor foi influenciada diretamente pelos períodos de polimento, sendo as resinas compostas nanoparticuladas as mais suscetíveis a alterações de cor após o envelhecimento térmico.
Effect of the polishing period on the surface of composite resins: analysis of optical.
Keywords: Dental polishing; Resinas compostas; Polimento dentário